Supporting employer branding by inbound marketing in Russia - Purmonen, Anna (My University, 2014)
The objective of this study is to understand how employer branding can be strategically supported by inbound marketing in Russia. Furthermore, the aim is to examine the special features of inbound marketing in Russia, as well as to learn what the most useful inbound marketing channels are in the Russian context. The theoretical background of this study is built from employer branding and inbound marketing literature. Inbound marketing is currently lacking a profound research on the topic and thus, this study contributes to the inbound marketing literature as well. The empirical data of this research is collected via three qualitative expert field interviews. The interviews were conducted between January and February 2014. Furthermore, a thematic content analysis was used in the process of analyzing the research results. Both the employer branding and inbound marketing are growing their importance in Russia. The results of this study suggest that a combination of employer branding and inbound marketing can bring companies competitive advantage over others in the Russian market. It is, however, crucial to first understand the peculiarities of the inbound marketing in Russia before taking it to the employer branding context. This study provides a framework for inbound marketing tools in Russia. The proposed framework takes into careful consideration the cultural factors affecting the selection of the inbound marketing tools in Russia. Furthermore, the results of this study suggest how inbound marketing could be successfully combined with employer branding in Russia in order to strengthen the employer brands in the Russian market. However, these results are mainly applicable in the Russian context. Therefore, additional research is needed in order to understand the relationship between the employer branding and inbound marketing in other cultural settings or in particular fields of business.